Observation of ηc(1S) and ηc(2S) decays to K+K−π+π−π0 in two-photon interactions - Amo Sanchez, Pablo del; Marks, Jörg; Uwer, Ulrich (Physical review. D, Particles, fields, gravitation, and cosmology, 2011)
We study the processes γγ→K0SK±π∓ and γγ→K+K−π+π−π0 using a data sample of 519.2fb−1 recorded by the BABAR detector at the PEP-II asymmetric-energy e+e− collider at center-of-mass energies near the Υ(nS) (n=2, 3, 4) resonances. We observe the ηc(1S), χc0(1P) and ηc(2S) resonances produced in two-photon interactions and decaying to K+K−π+π−π0, with significances of 18.1, 5.4 and 5.3 standard deviations (including systematic errors), respectively, and report 4.0σ evidence of the χc2(1P) decay to this final state. We measure the ηc(2S) mass and width in K0SK±π∓ decays, and obtain the values m(ηc(2S))=3638.5±1.5±0.8 MeV/c2 and Γ(ηc(2S))=13.4±4.6±3.2 MeV, where the first uncertainty is statistical and the second is systematic. We measure the two-photon width times branching fraction for the reported resonance signals, and search for the χc2(2P) resonance, but no significant signal is observed.
*The BABAR Collaboration: P. del Amo Sanchez, J. Marks, U. Uwer [und 439 weitere Personen]
Im Titel sind das Plus- und Minuszeichen sowie die Zahl 0 hochgestellt
Im Titel ist der Buchstabe c tiefgestellt
Gesehen am 06.10.2022